Rituals in Slavic Pre-Christian Religion Festivals, Banqueting, and Divination - Álvarez-Pedrosa, Juan Antonio (Beyond Medieval Europe, 2023)
The authors comprehensively analyze all the available information regarding the ritual practices of Slavic pre-Christian religion that can be found in written medieval texts. After investigating every kind of reference to such practices, they offer a reconstruction of Slavic pre-Christian religion on the basis of these medieval testimonies. In doing so, they overcome the challenges presented by the fact that all of these sources are indirect, since the Slavs did not acquire literacy until they became Christians. Thus the writers of these texts mostly professed a monotheistic religion, being Christians and in some cases Muslims. The picture that they offer is biased and determined by their own faith. The present analysis innovatively combines testimonies from every Slavic area (Eastern, Western, and Southern), showing their mutual correspondences and emphasizing the relationship between the Slavic pre-Christian religion and its Indo-European roots.